God and the Art of Happiness - Charry, Ellen T.. (Grand Rapids (Mich.): Eerdmans, 2010)
"After taking an introductory look at ancient Greek philosophy, Charry surveys the treatment of God and happiness throughout the history of Christian thought, from Saint Augustine through the 18th century. She then explores the biblical vision of happiness in the Pentateuch, Psalms, Proverbs and the Gospel of John, clearly showing how the Bible encourages the happiness and flourishing that accompany obedience to the Creator."
The Western philosophical heritage -- Saint Augustine of Hippo -- Anicius Manlius Severinus Boethius -- Saint Thomas Aquinas -- The modern fate of the doctrine of happiness -- Joseph Butler -- Doctrinal foundation -- Divine commands -- Asherism in the pentateuch -- Asherism in the psalter -- Reverent obedience: the witness of Proverbs -- Eternal life: the witness of the Gospel of John -- God and the art of happiness.
Keywords: Happiness -- Religious aspects&delete& -- Christianity&delete& -- History of doctrines; Obedience -- Religious aspects&delete& -- Christianity